2019
DOI: 10.31387/oscm0390243
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Green Supply Chain Drivers, Triple Bottom Line Sustainability and Operational Performance: An Empirical Investigation in The UK Manufacturing Supply Chain

Abstract: Sustainability has assumed salience over the past years, thereby becoming a corporate mantra as well as a promising research area. Most sustainability studies have focused on environment friendly operations contributing to the concept. However, sustainability extends beyond environmental performance to also encompass economic and social performance. All the three factors combine to form the 'Triple bottom line (TBL) performance'. This paper is an empirical investigation of the effect of green supply chain (GSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Social sustainability is a less explored area, as sustainable development often focuses on the environmental aspects of sustainability. Studies have primarily concentrated on the environmental dimension of sustainability, with fewer studies on the social dimension (Mohseni et al, 2019;Pattnaik & Pattnaik, 2019). All three dimensions of sustainability must be addressed to attain a holistic, sustainable outcome.…”
Section: Figure 1 Scope Of Supply Chain Managementmentioning
confidence: 99%
“…Social sustainability is a less explored area, as sustainable development often focuses on the environmental aspects of sustainability. Studies have primarily concentrated on the environmental dimension of sustainability, with fewer studies on the social dimension (Mohseni et al, 2019;Pattnaik & Pattnaik, 2019). All three dimensions of sustainability must be addressed to attain a holistic, sustainable outcome.…”
Section: Figure 1 Scope Of Supply Chain Managementmentioning
confidence: 99%
“…All of these aspects imply that company decisions, even regarding internal activities, must reflect consumer needs (Ta et al, 2015). More importantly, producer-consumer collaboration in the production process has begun (Pattnaik and Pattnaik, 2019). Boyce and Mano (2018) stated that the inclusion of end-users in corporate decision making makes it possible for consumers to select the suppliers they prefer.…”
Section: Internal Environmental Managementmentioning
confidence: 99%
“…Figure [2] depicts the high-level correlation between innovation and industrial output leading to increased industrial emissions, which in turn has led to increasing direct and indirect control measures to offset adverse impacts. The application of direct and indirect measures has resulted in the need for industry to shift focus away from the traditional economies of scale model (Smith & Skinner, 1982) manufacturing at the lowest cost price and selling at a higher price to maximize profits, towards enhanced awareness of the role of the organization across its own value chain and extended across wider analysis of societal and environmental impacts by reviewing as increasingly wider set of criteria for example reporting data on carbon footprint, human rights, hazardous chemicals, conflict mineral, critical raw materials, recycled material content (Pine & Gilmore, 1998;Tukker, 2015;Pattnaik & Pattnaik, 2019). Figure [5] showed that the respondents had a understanding of sustainability and the circular economy, however responses to (Q9) where respondents were asked to identify sustainability elements, from a list 15 potential answers, the strongest consensus was formed against elements relating to: (1) energy use; (2) renewable energy, and (4) recycling.…”
Section: Literature Review Summarymentioning
confidence: 99%
“…The Circular Economy from circa 2010, extended sustainability, by introducing the concept of open-loop systems, where products lifespans are extended significantly via the use of repairs, repurposing and recycling to generate new secondary raw materials to significantly reduce the amounts of waste ending up in landfill or incinerated to generate electricity (Zeng, et al, 2017;Ellen MacArthur Foundation, 2020;Pattnaik & Pattnaik, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation